The future of invasive terrestrial vertebrates in Europe under climate and land-use change. (11th March 2021) - Polaina, Ester; Soultan, Alaaeldin; Pärt, Tomas; Recio, Mariano R
Abstract: Predicting suitable locations for invasive alien terrestrial vertebrates (IATV) under different scenarios of global change is essential for local and transboundary management aimed to prevent the spread of invasions. Using a spatial modelling approach adapted to invasive species, we identify range-shifts in suitable areas for 15 of the most harmful IATV in Europe, considering future climate and land-use changes. We predict range contractions for seven of these IATV, expansion for four, and inconclusive outputs for the rest. For most Europe, future aggregated distributions show stable or decreasing trends in total IATV richness. Still, specific regions will increase their suitability for additional IATVs, including some protected and last-of-the-wild areas. Our results are informative for early decision-making and long-term strategies to prevent negative effects of IATV. Our approach is based on publicly available data, so predictions can be revised as new data becomes available.